INFLUENCE OF HIGH-DOSE ATORVASTATIN ON BILE ACID METABOLISM IN MICE WITH LIVER INJURY AND RELATED MECHANISM - XIA Feifei, SONG Bingxue, SONG Yuqing, TIAN Jiawei, YAN Hui, HUANG Yuxiao, XIN Hui, LIANG Hui (精准医学杂志, 2023)
Objective To investigate the influence of high-dose atorvastatin on bile acid metabolism in mice with liver injury and its mechanism. Methods A total of 40 specific pathogen-free male C57BL/6 mice were randomly divided into normal saline group (group A) and low-, middle-, and high-dose atorvastatin groups (groups B, C, and D, respectively), with 10 mice in each group. After 30 days of intragastric administration of normal saline and atorvastatin at a dose of 10, 20, and 30 mg/kg, respectively, orbital blood was collected from the mice in each group, and these groups were compared in terms of the serum levels of total bile acid (TBA), endotoxin (ET), aspartate aminotransferase (AST), and alanine aminotransferase (ALT); after liver tissue samples were collected, HE staining was performed to observe the pathological changes of liver tissue, and PCR was used to measure the mRNA expression levels of the bile acid metabolism-related genes farnesoid X receptor (FXR) and multidrug resis-tance-associated protein 2 (MRP2) in liver tissue. Results The mice in group D had slight swelling, sporadic inflammatory cell infiltration, and feather-like degeneration in liver tissue. Compared with the other groups, group D had significant increases in the serum levels of TBA, ET, AST, and ALT (P<0.05). Compared with group A, groups C and D had significant reductions in the relative mRNA expression levels of FXR and MRP2 in liver tissue (P<0.05), and compared with group B, group D had significant reductions in the relative mRNA expression levels of FXR and MRP2 in liver tissue (P<0.05). Conclusion Atorvastatin can induce the increase in serum TBA level in mice and lead to changes in the expression of the downstream FXR and MRP2 genes associated with bile acid metabolism in liver tissue, and abnormal bile acid metabolism in liver tissue caused by high-dose administration may be one of the main causes of atorvastatin hepatotoxicity.